Headache: tip of the iceberg. Issue 2 (20th February 2020) - Kommineni, Usha Bhanu; Krishnamurthy, Rashmi
Abstract : We report the case of a 64-year-old pseudophakic patient in a rural area who chronically suffered from headache with eye pain and was on analgesics for pain relief but never turned up to an ophthalmologist. There was lack of awareness to visit an ophthalmologist for headache as he thought that after undergoing cataract surgery, the role of ophthalmologist was limited. His approach to our centre was only after intense headache with sudden loss of vision. He had actually developed secondary glaucoma due to pupillary block angle closure as a late complication following yttrium aluminium garnet capsulotomy. After medical and surgical management, he regained his complete vision with total relief from headache.